Evidence based case report: Pyridoxine supplementation in children with pervasive developmental disorders - Sekarpramita Darmaputri; Tjhin Wiguna (Paediatrica Indonesiana, 2014)
Pervasive developmental disorders (PDD)is defined as a neurodevelopmental disorder,c haract erized by social withdrawal,communication deficits, and repetitivebehaviors. PDD include autistic disorder, Rett'ssyndrome, childhood disintegrative disorder, Asperger' ssyndrome, and pervasive developmental disorder nototherwise specified or atypical autism.1 Update ofepidemiological studies published between 1966 and2006 show reports of estimated prevalence for autismhas varied between 3 .31 and 86 children per 10,000, 2and predominantly occurs in males than females(male:female ratio = 4: 1) .3There is a hypothesis that behavioral problemsin children with pervasive developmental disorderare highly associated with the neurotransmitterimbalances. Therefore, psychotropic medications (eg.atypical antipsychotics, selective serotonin reuptakeinhibitors, and psychostimulants), which work ondopamine and serotonin receptors, are the FDAapprovedmedications for PDD.4 On the other hands,the use of novel, unconventional, and/or off- labeltreatments associated with the n eurotransmitterspathway for children with POD is increasing andmore common.